Safety profile of tranexamic acid during and after caesarean section - Usha Agrawal; Preshant Shrivastava (International Journal of Medical Research and Review, 2016)
Introduction: Delivery by caesarean section can cause many complications. The most common complications documented are primary and secondary postpartum hemorrhage. Tranexamic acid is a synthetic analogue of the amino acid lysine and its action is to reduce blood loss. Both antepartum and PPH are being treated by TXA extensively. The present study was undertaken to evaluate the efficacy and safety of tranexamic acid in reducing the blood loss during and after LSCS.Material & Methods: Hundred pregnant women undergoing LSCS were included in the study. Subject were allocated in two groups–1) Study group–50 Subject who received tranexamic acid. 2) Control group–50 Subject who did not received tranexamic acid.Results: There was no significant alteration in the vital signs of subjects following tranexamic acid administration at time of delivery & at 1 hr & 2 hr postpartum. In our study, not a single patient developed signs of thrombosis. The side effects of tranexamic acid as nausea, vomiting & diarrhea were not statistically significant in both the groups in our study. In our study, there was no statistical difference in APGAR score at 1 & 5 minutes of the baby in both the groups.Conclusion: Data analysis of our study suggests that tranexamic acid can be used safely in LSCS with no serious side effects, and without increasing the occurrence of thrombosis.